Effect of feed additives on shipping shrinkage of yearling heifers - Brazle, F.K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two studies were conducted to determine the effect of feed additives on the transit shrink of yearling cattle. In Trial I, 146 mixed-breed heifers were offered a mineral mixture containing either Terramycin® or Bovatec®, or without additive while grazing native grass pastures. Shrinkage after 300 miles in transit was lower (P<.09) for Bovatec-fed heifers than the other groups. In Trial II, 60 mixed-breed heifers were offered free choice prairie hay, plus soybean hulls without additive or containing either Aureomycin ®, Rumensin, or Bovatec®. Both ionophores tended to reduce live weight shrink following a 10-hour withholding of feed and water, but treatment differences were not significant (P>.05). The small shrinkage differences observed in these two trials would not justify changes in the weighing practices of feeder cattle.
Keywords: Beef; Shrink; Antibiotic; Ionophore; Feeder cattle